Miller Fisher syndrome with acute angle-closure glaucoma as the first manifestation: A case report. Issue 50 (December 2017) - Han, Jingzhe; Ji, Ye; Cao, Duanhua; Kang, Zhilei; Zhu, Jianguo
Abstract: Rationale: There were no reports of Miller Fisher syndrome (MFS) with acute angle-closure glaucoma as the first manifestation. Patient concerns: A 78-year-old female patient was admitted to our hospital with pain in her left eye, blurred vision along with nausea, and vomiting for 2 days. It was extremely rare that ophthalmoplegia, loss of tendon reflexes, and ataxia, did not occur in the early stages of MFS, and initial presentation was only dilated pupis and an increase in intraocular pressure. Diagnoses: The final diagnosis of the patient was MFS. Interventions: Intravenous immunoglobulins were administered. Outcomes: Ophthalmoplegia, walking instability, and ataxia gradually improved. At 3 months follow-up, there was no neurological deficit, and the patient could completely self-care. Lessons: This is the first report of MFS patient with acute angle closure glaucoma as the first manifestation. Consideration should be given to the possibility of incorporating autonomic nervous system dysfunction, or even MFS, in patients with acute angle-closure glaucoma in order to reduce missed diagnosis rate.